Understanding violence: the intertwining of morality, religion, capitalism and violence: a philosophical stance - Magnani, Lorenzo (Studies in applied philosophy, epistemology and rational ethics, 2024)
This book offers a philosophical account of violence, engaged with both empirical and theoretical debates in disciplines such as cognitive science, sociology, psychiatry, anthropology, political theory, evolutionary biology, and theology. The primary thesis is that violence is intertwined with morality and typically enacted for "moral" reasons. To show this, the book compellingly demonstrates how morality operates to trigger and justify violence and how people, in their violent behaviors, can engage and disengage with discrete moralities. The author's fundamental account of language, and in particular its normative aspects, is particularly insightful as regards extending the range of what is to be understood as violence beyond the domain of physical harm. By employing concepts such as "coalition enforcement", "moral bubbles", "cognitive niches", "overmoralization", and "military intelligence", the book aims to spell out how perpetrators and victims of violence systematically disagree about the very nature of violence. The author's original claim is that disagreement can be understood naturalistically, described by an account of morality informed by evolutionary perspectives as well. This book helps us come to terms with the fact that we are intrinsically "violent beings". To acknowledge this condition, and our stupefying capacity to inflict harm, is a responsibility we must face up to: such understanding could ultimately be of help in order to achieve a safer ownership of our destinies, by individuating and reinforcing those cognitive firewalls that would prevent violence from always escalating and overflowing. This second edition is thoroughly revised and integrated with two new chapters to cover new aspects of violence and its understanding, such as the role of looting finance in facilitating violent outcomes and the attack to scientific cognition and human creativity